Paternidades: perspectiva sócio-histórica e expressões em mídias sociais - Campoi, Rafael Candeloro (2022)
The present work analyzes paternity from a socio-historical perspective, using the framework of critical theory and having as an empirical basis the discourse produced on paternity in podcasts. Based on bibliographic research, it presents paternity as being socially and historically constructed and, therefore, linked to issues of generations, sex/gender, race/ethnicity and social class, which cross different institutions. In order to (re)congnize the debate about paternity in contemporary media, the podcast was used as a research field, because it is a powerful discursive universe of analysis for several areas of knowledge. Four episodes of the podcasts Mamilos and MEMOH were selected, whose selection was based on criteria based on the PodPesquisa 2019 — from which the profile of the podcast listener in Brazil was traced. From the universe of podcasts existing in the country, those that are aimed at the paternal audience stand out, among which four were selected, and whose producers were interviewed in order to outline the profile of those who produce podcasts aimed at fathers. The main findings of the research show that (1) the debate on paternity is part of the perspective of the need to establish other relationships — no longer those based on inequality and oppression; (2) that parenting is not disconnected from social and economic relationships, so that any change will not come from individual initiatives, or from a spontaneous collective awakening to new behaviors; and (3) that the reflections on paternity found in the research evidence the existence of a man-father model that, despite still being in force, its reproduction is not supported today. And, finally, this research brings the mark of originality by inserting the field of research, podcasts, as well as another bias of discussion about paternity - no longer those that evidence only the paternal absence - in the framework of academic productions of Social Work, with a view to encouraging social workers to rethink their daily practices when working with parental relationships